Survey of Civil Society Leaders in Mali - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
This dataset includes information collected face-to-face from 1,014 civil society organization (CSO) leaders from 48 communes in rural and urban Mali during January -- March 2021. The goal of the CSO leaders' survey is two-fold. We aim to measure several relevant characteristics distinguishing different CSOs from one another. Within each of these 48 communes, we used block randomization to select 20 or 24 CSOs, respectively. We blocked on CSO gender composition (all male, all female, or mixed) and CSO formality (formal or informal), creating six group types; we then selected at least four CSOs in the commune from each particular group type. The resulting sample of 1,020 CSOs (of which we were successfully able to interview 1,014) thus expresses substantial variation within each commune on both gender composition and formality.